The fear of childbirth: a study in the north of Portugal - Prata, Ana Paula (2016)
Childbirth is a universal phenomenon and a meaningful experience that has the potential to trigger developmental transitions, stress, anxiety and/or fear, which, at times, can negatively impact future childbirth experiences. An exploratory and descriptive study was conducted aiming to identify the levels of fear experienced by pregnant women associated with childbirth and their main causes. A convenience sample was selected. Data collection were carried out in an outpatient obstetric hospital in the northern region of Portugal, between July 2010 and July 2012. To evaluate the intensity of fear of childbirth a visual analogic scale of 10 points was applied. Interviews were conducted in order to identify the main causes of fear. Ethical approval and informed consent were obtained. Regarding the level of fear, the majority (98%) of pregnant women had fear of childbirth, 60.2% reported moderate fear and 28% intense fear. Anxiety, primiparity and lack of knowledge related to birthing were also found to increase the fear of childbirth. Some of the main causes of fear identified were: complications during childbirth; pain/suffering; not knowing how to cope with pain; not able to give birth; baby with malformation/disease and/or suffering. Most women feel moderate or intense fear of childbirth and this is associated to well identified causes with high impact on the woman and family. To minimize the effects of fear, an early intervention has to be considered, including childbirth education classes where nurses can address and work women’s fear in order to minimize it and promote a more positive experience.